MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN HOTEL PADA MASA PANDEMI COVID-19 - Ni Nengah Rupadi Kertiriasih; Tiksnayana Vipraprastha (Jurnal Ilmiah Satyagraha, 2022)
This study aims to determine whether motivation and job satisfactionhave an impact on the performance of hotel employees during the Covid-19pandemic. The sampling technique in this study uses a Non-Probability Samplingmethod where all the population is used in the study. The data analysis techniqueused in this research is multiple regression analysis. The results of this studyindicate that: (a) there is a significant and positive effect between the motivationand performance of hotel employees with a coefficient value of 0.527 and asignificance value of 0.000, and (b) there is a significant and positive effectbetween job satisfaction and hotel employee performance. with a coefficient valueof 0.294 and a significance value of 0.013.